Synthesis of polyacrylic acid-citrate-amorphous calcium phosphate and its effect on dentin remineralization - CHEN Yinying, CHEN Chen (Kouqiang yixue)
Objective To prepare and identify the polyacrylic acid-citrate-amorphous calcium phosphate composite (PAA-Cit-ACP), and analyze its effect on dentin remineralization. Methods PAA-Cit-ACP was prepared by co-precipitation and freeze-drying methods. The composite was characterized by FTIR, XRD, Zeta potential, SEM, TEM and SAED. SEM was used to analyze the effect of PAA-Cit-ACP on dentin remineralization. Cell cytotoxicity of PAA-Cit-ACP was evaluated by CCK-8 method. Results The characteristic peaks of carboxyl (1 567 cm-1 and 1 416 cm-1) and ACP (1 064 cm-1 and 563 cm-1) were simultaneously observed in the FTIR spectrum, and the XRD and SAED results confirmed its amorphous state. The Zeta potential of PAA-Cit-ACP was -18.47 mV. PAA-Cit-ACP appeared as spherical nanoparticles according to SEM and TEM. In SEM images, a large amount of new minerals formed on the surface of demineralized dentin after PAA-Cit-ACP treatment. The CCK-8 result showed that PAA-Cit-ACP exhibited good biocompatibility at a concentration of 250, 500, and 1 000 μg/mL. Conclusion Citrate can co-stabilize supersaturated calcium phosphate solutions with polyacrylic acid, forming polyacrylic acid citrate amorphous calcium phosphate which can promote dentin remineralization.